Mapping Early Modern Japan : Space, Place, and Culture in the Tokugawa Period, 1603-1868 - Yonemoto, Marcia, 1964- (Book collections on Project MUSE., 2003)
This elegant history considers a fascinating array of texts, cultural practices, and intellectual processes-including maps and mapmaking, poetry, travel writing, popular fiction, and encyclopedias-to chart the emergence of a new geographical consciousness.